St. Vincent wharf, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (D.Adamson, Stationer, [Trinidad and Tobago], 2011)
The postcard shows fishing boats anchored in the Port of Spain habour also known as the St.Vincent Jetty
Colour: Sepia; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Fishing boats; Harbors; Cities and towns--Port of Spain